The design of the cemented stem influences the risk of Vancouver type B fractures, but not of type C: an analysis of 82,837 Lubinus SPII and Exeter Polished stems - Chatziagorou, Georgios; Lindahl, Hans; Kärrholm, Johan (Acta Orthopaedica, 2019)
Background and purpose — In total hip replacements, stem design may affect the occurrence of periprosthetic femoral fracture. We studied risk factors for fractures around and distal to the 2 most used cemented femoral stems in Sweden. Patients and methods — This is a register study including all standard primary Lubinus SPII and Exeter Polished stems operated in Sweden between 2001 and 2009. The outcome was any kind of reoperation due to fracture around (Vancouver type B) or distal to the stem (Vancouver type C), with use of age, sex, diagnosis at primary THR, and year of index operation as covariates in a Cox regression analysis. A separate analysis of the primary osteoarthritis patient group was done in order to evaluate eventual influence of the surgical approach (lateral versus posterior) on the risk for Vancouver type B fractures. Results — The Exeter stem had a 10-times (95% CI 7–13) higher risk for type B fractures, compared with the Lubinus, while no statistically significant difference was noticed for type C fractures. The elderly, and patients with hip fracture or idiopathic femoral head necrosis, had a higher risk for both fracture types. Inflammatory arthritis was a risk factor only for type C fractures. Type B fractures were more common in men, and type C in women. A lateral approach was associated with decreased risk for Type B fracture. Interpretation — Stem design influenced the risk for type B, but not for type C fracture. The influence of surgical approach on the risk for periprosthetic femoral fracture should be studied further.